Internet of Things (IoT): Masa Depan Kehidupan Serba Terkoneksi - Gautama, Nevy; Yunita, Yura; Hidayat, Ajrin (Primary Journal of Multidisciplinary Research, 2025)
The Internet of Things (IoT) is one of the most significant milestones in modern technological development, enabling physical devices to connect to the internet and communicate with each other automatically. The emergence of IoT introduces a new paradigm in everyday life, from smart homes and smart cities to integrated transportation systems and digital healthcare services. This integration not only enhances convenience but also improves efficiency in terms of energy, time, and cost. In the industrial sector, IoT is a key driver of Industry 4.0, where automation and real-time data analysis enhance productivity and product quality. In healthcare, IoT applications allow remote patient monitoring through wearable devices connected to medical systems, supporting faster and more effective healthcare services. Meanwhile, in agriculture, IoT contributes to precision farming by monitoring soil moisture, temperature, and nutrient requirements, ultimately increasing crop yields in a sustainable manner. Nevertheless, the development of IoT also presents serious challenges, particularly regarding cybersecurity, data privacy, and the readiness of network infrastructure across different regions. Without proper regulations and clear security standards, IoT utilization may lead to significant risks. Therefore, collaboration among governments, industries, and academia is necessary to design sustainable, secure, and inclusive IoT development strategies. With the right approach, IoT has the potential to become one of the main pillars in building a digital ecosystem that supports a fully connected life in the future.